EFFICACY OF GRIP STRENGTH AND HAND COORDINATION TRAINING IN IMPROVEMENT OF HANDWRITING IN SCHOOL CHILDREN.â€ - Bharthu, Rehana (Innovare Journal of Education, 2017)
ABSTRACT Background: Proficient handwriting is critical for education and child's performance during academics. Students who struggle to acquire handwriting skills may experience frustration and anxiety, which in turn may negatively affect overall school performance. Studies of handwriting for typically developing children in grades 1 to 5 have found the quality of handwriting develops quickly during grade one (ages 6-7y typically) and reaches a plateau by grade two (age 7–8y typically). It was found that grip force i.e. grip strength and motor coordination are underlying mechanism for poor handwriting. There is little known about the effectiveness of physiotherapy treatment on improvement of handwriting. So the need arise to find out the ‘efficacy of grip strength and hand coordination training in improvement of handwriting in school children'. Objectives: The purpose of the study is to evaluate the efficacy of grip strength training and hand coordination training in the improvement of handwriting. Methodology: This study is a randomized controlled trial of 30 school going children who were having Handwriting problem diagnosed from Handwriting Proficiency Screening Questionnaire (HPSQ).Children are than randomly divided into 2 groups, Group A (experimental Group) which consists of a grip strengthening and motor coordination exercises. And Group B (Control Group) consists of Ergonomics advice on handwriting and was taught appropriate writing posture by therapist and teachers. An activity of this group includes writing activities with different pencils, grasps, papers etc. The Handwriting quality was evaluated using Minnesota Handwriting Assessment (MHA). Results: The results of the present study showed that experimental group showed statistically significant results in improvement of handwriting. Conclusion: It can be concluded that a well planned physiotherapeutic program can help to improve the handwriting quality of school going children over a short period of time and thus help the child to improve his self-confidence and his academic results. Key words: Handwriting, Grip strengthening exercises, motor coordination exercises, Handwriting proficiency screening questionnaire, and Minnesota handwriting Assessment tool